A Report of 150 Cases of Cervical Lymphadenopathy - QAISAR KHAN INAYAT ULLAH KHAN, ASGHAR ULLAH KHAN (Journal of Fatima Jinnah Medical University, 2018)
Background: The head and neck has extremely rich lymphatic drainage, an enlarged neck node is a common clinical observation and the differential diagnosis is wide, ranging from simple benign conditions to malignancy, a systematic approach for its diagnosis is important. Objective: To find out frequency and pattern of different pathologies involving cervical lymph nodes and proper diagnostic protocol for their early definitive treatment. Patients and Methods: This prospective descriptive study was conducted at the ENT Departments of Khyber Teaching Hospital, Peshawar from June 2002to Dec. 2009. A total of 150 patients were included in this study. Fine needle aspiration cytology (FNAC) was primarily carried out in all cases while biopsy i.e. incisional/excisional performed in cases where FNAC was inconclusive or to confirm diagnosis of malignancy. Results: Total 150 Patients aged 3-74 years with a mean of 35.44±17.06. The male to female ratio was 1.2:1. Tuberculosis was the most common cause of cervical lymphadenopathy in 54 (36%)cases, followed by metastasis in 44 (29.33%)cases, reactive hyperplasia 28(18.66%)cases and lymphoma in 22 (14.66%)patients, including 10(6.67%) cases of Hodgkin's lymphoma and 12(8%) cases of non-Hodgkin's lymphoma. 2 (1.33%) patients had Kikuchi lymphadenitis, 1 (0.67%) patient had sarcoidosis. The FNAC accuracy was 86% in (128/150) cases 42(28%) patients needed open biopsy to reach a final diagnosis. Conclusion: Tuberculosis was found the commonest cause of cervical lymphadenopathy followed by metastatic nodes, reactive hyperplasia/chronic non specific inflammation, lymphoma, Kikuchi and sarcoid lymphadenitis. Early accurate diagnosis is important for appropriate treatment of the underlying condition and prevents unnecessary complications. FNAC is a reliable diagnostic tool and should always be considered before biopsy.